Peningkatan Hasil Belajar Peserta Didik Menggunakan Pendekatan Saintifik pada Pembelajaran Tematik Terpadu di Kelas I Sekolah Dasar - Septiani, Indah Riandi; Harni, Harni (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2019)
The purpose of this research is to describe the planning, implementation and improvement learning outcomes of students using a problem based learning model in integrated thematic learning in grade I Elementary School. In this study applying the type of PTK research uses qualitative and quantitative approaches. Where this research was conducted on class I B SDN 34 Simpang Haru Padang totaling 29 people consisting of 14 male students and 15  female students. The results of the study in the first cycle of learning outcomes reached a percentage of completeness of 25% (Less category) with an average value of 3.12 (good category) increased in the second cycle percentage of completeness 90% (very good category) with an average achievement of 3.75 (very good category).